Response of drainage to tectonics and PS-InSAR derived deformation study in Bilaspur, northwestern Himalaya, India - Moulishree Joshi; Girish Ch Kothyari; Kapil Malik; Ajay Kumar Taloor (Geodesy and Geodynamics, 2022)
The study of drainage patterns in tectonically active regions is conducive to the prediction of regional geomorphology. Subtle subsurface changes can be detected by drainage conditions and manifested in the form of drainage anomalies. The Satluj valley of Bilaspur, which is traversed by numerous faults in northwest Himalayan region, was selected to analyze the effect of active tectonics on drainage evolution. With the Persistent Scatterer Interferometric Synthetic Aperture Radar (PS-InSAR) technique, SENTINEL-1A data were used to estimate the active surface deformation between September 2015 and December 2020. The results show that the region between Barasar Thrust (BrT) and Main Central Thrust (MCT) is undergoing deformation of ±12 mm/yr. The Stream Power Incision Model (SPIM) was used to predict deformation patterns. To validate the tectonic activity generated by the drainage network, seismic b-values were calculated, indicating the accumulating stresses. This study shows the importance of drainage anomalies in tectonically active areas. When used in close combination with other seismotectonic parameters, drainage anomalies can be effective in delineating tectonically active regions.